Courts and diversity : twenty years of the constitutional court of Indonesia - De Villiers, B. (Bertus); Isra, Saldi; Faiz, Pan Mohamad (Brill/Nijhoff, 2024)
"The Constitutional Court of Indonesia functions in one of the most diverse societies in the world. It is required to resolve disputes within a kaleidoscope of diversity and plurality with flexibility, pragmatism, asymmetry, and wisdom. Whilst national minimum norms are important for nation-building, recognition of local customs, diversities and indigenous systems are equally important to protect the territorial integrity of Indonesia and ensure local peace and stability. Responding to demands of religious plurality, customary lands rights, traditional voting systems, decentralisation to regions and local governments, and responding to diversity of community life, requires extraordinary skill, insight and flexibility. This book gives insight into twenty years of jurisprudence and places it in an international comparison"-- Provided by publisher.
Includes index.
Keywords: Indonesia. -- Mahkamah Konstitusi.; Constitutional courts -- Indonesia.; Cultural pluralism.; Cours constitutionnelles -- Indonésie.; Diversité culturelle.